Analisis Framing Berita Kasus Korupsi Timah: Dampak Kerugian Negara Rp271 Triliun pada Kompas.com dan Detikcom - Nabilla, Amyra Shasya; Muharromah, Noer Nazwa; Putri, Valentina Kusmila (Tuturlogi: Journal of Southeast Asian Communication, 2024)
This research analyzes the media coverage framework related to the tin corruption case that caused the state to incur losses of Rp271 trillion. Through a framing analysis approach, this study investigates how the mass media constructs and portrays the corruption case. Data were collected from various media sources to understand the diversity of perspectives presented by different media outlets. This analysis also considers the impact of the frames used by the media on public perception of corruption and law enforcement efforts. The findings of this research can serve as a basis for promoting more responsible and objective journalism practices, as well as strengthening public trust in the media's integrity in reporting corruption cases and justice. By delving deeper into the impact of media framing on public perception, this research provides a strong foundation for efforts to increase public awareness of the importance of transparency and accountability in news presentation. The results of this study indicate that Kompas.com and Detik.com have different framework approaches in reporting the Tin corruption case. Kompas.com tends to provide in-depth analysis and comprehensive understanding of complex issues such as corruption, while Detik.com focuses more on actual news with an emphasis on the context and current developments of an event.